Effect of freeze-thaw cycles on the response of roller compacted concrete pavement reinforced by recycled polypropylene fibre under monotonic and cyclic loadings. Issue 12 (2nd December 2021) - Haghnejad, Mehdi; Modarres, Amir
Abstract : The present research focused on the effect of freeze-thaw cycles on behaviour of roller-compacted concrete pavement (RCCP) reinforced with recycled polypropylene fibres. RCCP specimens were designed with dry aggregates, four water to cement ratios of 0.3, 0.4, 0.5 and 0.6 and four fibre dosages of 0, 1, 3 and 5 kg/m 3 . Experiments were performed before and after exposure to freeze-thaw cycles in the presence of de-icing salt. The main experiments included the workability test by measuring the Vebe time, the ultrasonic pulse velocity (UPV), the modulus of rupture and the fatigue resistance with three-point bending method. Based on the results of the UPV test, which was performed before freeze-thaw cycles, and every 60 cycles up to 300 cycles, the specimens designed with water to cement ratios of 0.4 and 0.5 and reinforced with 1 kg/m 3 fibre had better performance than other reinforced RCCPs. Modulus of rupture and fatigue tests were conducted after 0, 150 and 300 freeze-thaw cycles. The results of the modulus of rupture tests were largely similar to the UPV test. In contrast, given to the fatigue test results, the specimens containing 1 and 3 kg/m 3 fibre exhibited similar behaviour after being exposed to freeze-thaw conditions and had a higher fatigue life than unreinforced specimens and those reinforced with 5 kg/m 3 fibre. According to the results of monotonic and cyclic loadings, RCCPs with water to cement ratios of 0.4 and 0.5 and fibre contents of 1 and 3 kg/m 3 are recommended to be used in real practice.